1999
DOI: 10.1096/fasebj.13.13.1825
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping and functional analysis of a polymorphic (CCTTT)nrepeat of NOS2A in diabetic retinopathy

Abstract: Accumulating evidence shows that the severity and rapidity of onset of diabetic retinopathy are influenced by genetic factors. Expression of the nitric oxide synthases is altered in the retinal vasculature in the early stages of diabetic retinopathy. We analyzed the allele distribution of a polymorphic pentanucleotide repeat within the 5' upstream promoter region of the NOS2A gene in samples of diabetic patients. In diabetic patients from Northern Ireland, the 14-repeat allele of the NOS2A marker was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
2
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(131 citation statements)
references
References 38 publications
8
114
2
7
Order By: Relevance
“…Of note no linkage disequilibrium (LD) was found between the two markers. Furthermore, we did not observe any relationship between the NOS2 variants and the clinical characteristics of RA, however, there are some data showing associations of the NOS2 promoter polymorphism with severe clinical manifestations of IDDM, such as retinopathy 10 and nephropathy. 17 Several reports have shown that NO overproduction plays an important role in autoimmunity and inflammation, 3 but the pathologic processes involved are complex and studies reported so far have been unable to assess the relative importance of NO in relation to other cytokine mediators.…”
Section: Resultscontrasting
confidence: 80%
See 4 more Smart Citations
“…Of note no linkage disequilibrium (LD) was found between the two markers. Furthermore, we did not observe any relationship between the NOS2 variants and the clinical characteristics of RA, however, there are some data showing associations of the NOS2 promoter polymorphism with severe clinical manifestations of IDDM, such as retinopathy 10 and nephropathy. 17 Several reports have shown that NO overproduction plays an important role in autoimmunity and inflammation, 3 but the pathologic processes involved are complex and studies reported so far have been unable to assess the relative importance of NO in relation to other cytokine mediators.…”
Section: Resultscontrasting
confidence: 80%
“…The multiallelic (CCTTT) n repeat is on the contrary an attractive disease-causing candidate, being a highly polymorphic marker with a recently suggested effect in NOS2 transcription. 10 Highly significant differences have been reported in the CCTTT allele frequencies between ethnically diverse populations. 15 The observed frequencies of this marker in our cohort of 199 healthy subjects from southern Spain fell within the Caucasian pattern 15 showing 11 different alleles (repeat and bp ranges 7-17 and 171-221 respectively) in unimodal distribution with the peak at the 12 repeat allele (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations